Drawn to the flame : teachers' stories of burnout - Singer, Erin A.; Etchells, Matthew J.; Craig, Cheryl J. (Emerald Publishing Limited, 2023)
Teacher attrition and burnout have been researched in school districts all over the country for several decades. Characterised by physical and psychological exhaustion, cynicism (as an interpersonal and emotional indication of built-up aggression), and a sense of helplessness and low self-efficacy, burnout can lead to anxiety, depression, diminished job performance, absenteeism, and attrition. Drawn to the Flame investigates incidences of burnout and burnout avoidance among educators in both K-12 and higher education spheres during the COVID-19 pandemic - a period that saw an intensification and increased frequency of polarizing sociocultural and socio-political conditions, resulting in psychosocial and emotional strain among those invested in education. Through narrative inquiry, the chapters present the stories of teachers in a variety of settings (e.g. urban, suburban, rural) and sociological conditions (economic, racial, sex/gender), who experienced first-hand the impact of the pandemic and the chaotic transition to remote learning, the impact of the U.S. Immigration and Customs Enforcement (ICE) and racial strife, on students and curricular planning processes.
Includes index.
Keywords: Teachers -- Job stress -- United States.; Teachers -- United States -- Psychology.; Burn out (Psychology) -- United States.; Education, Teacher Training & Certification.; Teaching skills & techniques.; elektronické knihy; electronic books